Are steroids required in the treatment of ganglion impar blockade in chronic coccydynia? a prospective double-blinded clinical trial - YOLCU, GÜNAY; GÜNDÜZ, OSMAN HAKAN (KOREAN PAIN SOC, 2019)
Background: Ganglion impar blockade is a reliable and effective treatment option used in patients with coccydynia. Our primary objective was to specify the role of corticosteroids in impar blockade. We compared applications of local anesthetic with the local anesthetic + corticosteroid combination in terms of treatment efficiency in patients with chronic coccydynia. Methods: Our study was a prospective randomize double-blind study. The patients were divided into 2 groups after randomization. The first group (group SL) was made up of patients where a corticosteroid + local anesthetic were used during ganglion impar blockade. In the second group (group L) we used only local anesthetic. We evaluated numeric rating scale (NRS) and Beck depression scale, which were employed before the procedure and in 1st and 3rd months after the procedure. Results: Seventy-three patients were included in the final analysis. We detected a significantly greater decrease in NRS values in the 1st month in group SL than in group L (P = 0.001). In the same way, NRS values in the 3rd month were significantly lower in the group with steroids (P = 0.0001). During the evaluation of the Beck test, we detected significantly greater decreases in the 1st month (P = 0.017) and 3rd month (P = 0.021) in the SL group than in the L group. Conclusions: Ganglion impar blockade decreases pain in the treatment of chronic coccydynia and improve depression. Addition of steroids in a ganglion impar blockade is required for treatment response that should accumulate over a long period of time.
Keywords: Adrenal Cortex Hormones; Anesthetics, Local; Beck Test; Coccygeal Pain; Depression; Ganglion Impar Blockade; Pain; Rating Scale; PAIN; COCCYGODYNIA; CORTICOSTEROIDS; MECHANISMS; ETIOLOGY; RECEPTOR